Tailoring spin defects in diamond by lattice charging - Felipe Fávaro de Oliveira (Nature Portfolio, 2017)
Ion implantation is used to introduce spin defects in solids, but it inflicts residual lattice damage, degrading performances. Here the authors demonstrate that the charge state of induced defects influences such damage, and that charging vacancies leads to improved coherence times and yield of centres.